Role of the Plasma Membrane Transporter of Organic Cations OCT1 and Its Genetic Variants in Modern Liver Pharmacology - Lozano, Elisa (Hindawi Publishing Corporation, 2013)
Changes in the uptake of many drugs by the target cells may dramatically affect the pharmacological response. Thus, downregulation of SLC22A1, which encodes the organic cation transporter type 1 (OCT1), may affect the response of healthy hepatocytes and liver cancer cells to cationic drugs, such as metformin and sorafenib, respectively. Moreover, the overall picture may be modified to a considerable extent by the preexistence or the appearance during the pathogenic process of genetic variants. Some rare OCT1 variants enhance transport activity, whereas other more frequent variants impair protein maturation, plasma membrane targeting or the function of this carrier, hence reducing intracellular active drug concentrations. Here, we review current knowledge of the role of OCT1 in modern liver pharmacology, which includes the use of cationic drugs to treat several diseases, some of them of great clinical relevance such as diabetes and primary liver cancer (cholangiocarcinoma and hepatocellular carcinoma). We conclude that modern pharmacology must consider the individual evaluation of OCT1 expression/function in the healthy liver and in the target tissue, particularly if this is a tumor, in order to predict the lack of response to cationic drugs and to be able to design individualized pharmacological treatments with the highest chances of success.